Managing Ta'awun in post normal times with spirituality: the case of social enterprises in Malaysia - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi (Meso Publishing, 2020)
The post normal business world is full with dynamism. The dynamism in business world has motivated enterprises to cooperate with other enterprises instead of competing with them. This trend is encouraged by the global initiative through United Nation’s Sustainable Development Goals (SDG). The world is no longer afforded to compete with the same limited resources for optimum benefit to the world. Sustainability of social enterprises is essential to give sustainable competitive advantage to the local economy. The ultimate aim of social enterprise is to deliver economic and social benefits to the community. This study postulates that the spirit of ta’awun (mutual cooperation) in social enterprises with enterprise spirituality has the ability to sustain social enterprises in Malaysia. The main objective of the study is to explore the ta’awun enterprise spirituality experience of social entrepreneurs. The study obtained feedback about the ta’awun enterprise spirituality experience from social entrepreneurs through personal interview. The results of the study suggest that ta’awun enterprise spirituality occurred in formal and informal transactions among social entrepreneurs.